Two-year prevalence of minor aphtha in Tabriz, Northwest Iran - Mahmood Sina; Mahmood Toorchi; Sepideh Vosough Hosseini; Ali Taghavi Zenouz; Masoumeh Mehdipour (Journal of Dental Research, Dental Clinics, Dental Prospects, 2009)
Background and aims. Recurrent aphthous stomatitis is a condition comprised of oral painful ulcers appearing at intervals in different intraoral sites, triggered by a variety of causative agents in certain subgroups of patients. Since there are no studies on the subject in Northwest Iran, the aims of the present study were to evaluate the prevalence of aphthous ulcer and to assess the association of some influencing factors on minor aphtha.
Materials and methods. Of all patients examined during a two-year period, 33 patients were diagnosed with aphthous lesions. A questionnaire was used to collect the data including age, gender, familial history, smoking habit, and food allergy of the patients. Chi-square test was used to assess the association of variables.
Results. The prevalence of aphthous lesions was found to be 0.3%, and was significantly higher in females compared with males (23 females and 10 males, respectively; P = 0.024). Familial involvement of aphthous ulcer was reported in 42.4% of the patients (P = 0.411). The aphthous ulcer was seen less frequently in smokers compared with non-smokers (P = 0.024).
Conclusion. A relatively low prevalence of minor aphtha was found in the studied population. Higher prevalence in females and non-smokers were observed.